Knowledge, attitudes, and practices towards poultry handling and Salmonella risk among households in Beirut, Lebanon - Dana Ataya; Christelle F. Iskandar; Samer A. Kharroubi; Mohamad T. Farran (Journal of Agriculture and Food Research)
Food-Borne Disease (FBD) is defined as an illness resulting from consuming foods contaminated with bacteria, their toxins, viruses, or parasites. Food poisoning due to improper food handling is a major global public health problem. In Lebanon, numerous challenges affect safe food consumption, with poultry being a common vehicle for many pathogens, such as Salmonella spp. This bacterium can cause serious illnesses, including gastroenteritis, characterized by abdominal pain, vomiting, diarrhea, and fever. This study aimed to examine the Knowledge, Attitudes, and Practices (KAPs) towards poultry handling among households in Beirut, Lebanon, and identify factors influencing KAP levels. A cross-sectional study was conducted through face-to-face interviews with 125 households in different areas of Beirut. The interview was divided into four main parts: sociodemographic characteristics, knowledge, attitudes, and practices. The results showed that consumers' knowledge and practices were inadequate, though their attitude was positive. Participants aged 43–55 had higher odds of having a good knowledge level than those aged 18–29 (OR = 3.889, p = 0.02). Additionally, those with a college education were 7.442 times more likely to have a positive attitude towards food safety compared to those with no formal education (p = 0.005). Most participants (91.2 %) do not regularly check their refrigerator and freezer temperatures. Furthermore, significant associations (p < 0.001) existed between the different KAP levels. This study aimed to raise public awareness regarding the handling of chicken to minimize food-borne illnesses by evaluating food handlers’ knowledge and behaviors. Insights from this study can used in campaigns to raise awareness about Salmonella and transmission risks among households. Moreover, findings may guide policymakers to create regulations for safe handling of poultry.